Pseudomama in dorso-lumbar region in man. Case report - Lidia Torres Aja; Julián Viera Llanéz; Neylín Caballero Aja (Medisur)
Supernumerary breasts are different forms of presentation according to the histological components that they pose. They are located mainly in axillary region, epigastric supraumbilical and other areas of the anterior chest wall, where the old lines of milk were. A case of a male patient, aged 39, was admitted to the provincial consultation each breast, presenting an increase in volume of a marble, from its birth on her back. On physical examination is evidence of the presence of a small breast in the patient's right dorsal region, it is a pseudomama, variety in the breast tissue is replaced by fat and to a location in the lumbar region, after checking preoperative into the operating room so it is necessary to perform the excision of the rudimentary breast. Reviewed the literature on the subject is not found similar evidence reported, so this case is considered as of great scientific interest.